Trends in Location of Death Among Older Adult Americans After Falls. (22nd April 2022) - Cross, Sarah H.; Anderson, David M.; Cox, Christopher E.; Agarwal, Suresh; Haines, Krista L.
Introduction: Fall-related mortality is increasing among older adults, yet trends and changes in the location of fall-attributed deaths are unknown; additionally, potential disparities are understudied.Methods: To assess trends/factors associated with place of death among older adult fall deaths in the US, a cross-sectional analysis of deaths using mortality data from 2003–2017 was performed.Results: Most deaths occurred in hospitals, however, the proportion decreased from 66.4% ( n = 9, 095) to 50.7% ( n = 15, 817). The proportion occurring in nursing facilities decreased from 15.9% ( n = 2175) to 15.3% ( n = 4, 778), while deaths at home and in hospice facilities increased. Male, Black, Native American, and married decedents had increased odds of hospital death.Conclusion: As fall deaths increase among older adults, end-of-life needs of this population deserve increased attention. Research should explore needs and preferences of older adults who experience falls and their caregivers to reduce disparities in place of death and to ensure high quality of care is received.